1999
DOI: 10.1016/s0009-9236(99)80181-7
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of linezolid in subjects with a range of renal function

Abstract: Clinical Pharmacology & Therapeutics (1999) 65, 162–162; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2001
2001
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Linezolid pharmacokinetics are not significantly altered, and dosage adjustments are unnecessary for patients with renal insufficiency 12 ; however, it is recommended that linezolid be administered after hemodialysis. 12,13 Reports of linezolid disposition in patients receiving CRRT have appeared, to our knowledge, in only one published abstract. 18 We obtained these serum and effluent linezolid values in our patient to ensure that his serum trough concentrations were therapeutic and to determine the extent of linezolid clearance by CVVHDF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Linezolid pharmacokinetics are not significantly altered, and dosage adjustments are unnecessary for patients with renal insufficiency 12 ; however, it is recommended that linezolid be administered after hemodialysis. 12,13 Reports of linezolid disposition in patients receiving CRRT have appeared, to our knowledge, in only one published abstract. 18 We obtained these serum and effluent linezolid values in our patient to ensure that his serum trough concentrations were therapeutic and to determine the extent of linezolid clearance by CVVHDF.…”
Section: Discussionmentioning
confidence: 99%
“…12 One study reported a dialysis extraction ratio of 38% that remained constant throughout the dialysis session. 13 However, the elimination rate constant did not change, and the authors concluded that no linezolid dosing adjustment is necessary in patients receiving intermittent hemodialysis. 13 Given that linezolid is removed by intermittent hemodialysis and has a small molecular weight (337 daltons), it is possible that a significant amount of linezolid is removed during CRRT, which provides renal replacement therapy 24 hours/day.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dosage adjustment is not necessary in patients with mild to moderate impaired renal function and liver disease, while patients on hemodyalisis should receive the linezolid dose after the dialysis session or a supplemental 200 mg dose of linezolid at the end of dialysis [9]. In volunteers, unchanged linezolid accounted for 90% of the circulating dose, with the major metabolite accounting for 56%.…”
Section: Metabolism and Eliminationmentioning
confidence: 99%
“…The elimination half-life was 4.5± 5.5 h under single dose and steady state conditions. Dosage adjustment is not necessary in patients with mild to moderate impaired renal function and liver disease, while patients on hemodyalisis should receive the linezolid dose after the dialysis session or a supplemental 200 mg dose of linezolid at the end of dialysis [9]. The influence of severe hepatic impairment on the pharmacokinetic profile of linezolid has not been established [10].…”
Section: Metabolism and Eliminationmentioning
confidence: 99%